Identifying motivation factors of the participation of local community in tourism industry in National Park, Pahang, Malaysia - Hassan Zaki, Pakhriazad; Awang, Khairil Wahidin; Ismail, Mohd Hasmadi; M. R., Noorhayati (2015)
This study attempt to identify and elaborate a motivation factors influence participation of local community in tourism industry in Kuala Tahan National Park, Pahang, Malaysia. Using random stratified sampling techniques, a total of 400 respondents were selected from seven villages in Kuala Tahan National Park. A theory of push and pull factor were applied in this study. Results showed that most of the local communities were more motivated by pull factors. The motivation by pull factor is due to reasons this tourism industries offers jobs to local peoples. They realize the tourism activities are one of fastest growing economy in their area and provide an employement in order to augment their socioeconomic.